CORRELATING INSOMNIA WITH EMOTIONAL INTELLIGENCE AND STRESS IN UNDERGRADUATE STUDENTS: A CASE STUDY AT LUMHS - Taskeen Waheed; Shams ur Rehman; Sunaa Zainab; Sorath Mustafa Dahri; Muhammad Owais; Dr Arsalan Ahmed Uqaili (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Insomnia is a multifactorial disorder mostly caused by psychological stress. Medical students tend to experience great loads of academic stress which leads to sleep disturbance. It has been found that stress has a significant negative correlation with emotional intelligence. This study aims to access the association among Insomnia, psychological stress and emotional quotient among medical undergraduate students. Methodology: This comparative cross sectional study was limited to students of LUMHS, which included 167 participants. The data was collected through simple convenient sampling by using Regensburg’s insomnia scale, perceived stress scale and emotional intelligence questionnaire to access the quality of sleep, stress levels and emotional quotient among undergraduate students respectively. Whole data was analyzed in SPSS (version 22.0). Results: The study found out that 57.6% of medical students were insomniac. Analysis showed a positive significant relation between insomnia and EI with p<0.01. While no significant negative relation existed between stress and insomnia with p=0.056. Stress and EI shared a significant negative association with p=0.007. Conclusions: Disturbed sleep and high stress levels individually affects one’s emotional intelligence, but short term insomnia is not found to have association with stress levels